Cerebral lipiodol embolisation. Issue 1 (11th September 2021) - Batcheller, Lisa; Thaller, Mark; Wright, Ben
Abstract : Cerebral lipiodol embolisation is a rare but serious complication of lymphangiography. A man in his seventies had undergone lymphangiography for a refractory chyle leak following oesophagectomy. The day after lymphangiography, his conscious level dropped with bilaterally miotic pupils, increased muscle tone and double incontinence. CT scan of the head showed patchy high density throughout basal ganglia, cortex and cerebellum but no infarct, in keeping with lipiodol embolisation. He was managed initially in intensive care and subsequently underwent thoracoscopy with clipping and suturing of the left thoracic duct, and later a talc pleurodesis. At 3 months, he had some cognitive limitations and was walking with a stick.